2010
DOI: 10.1038/cdd.2010.42
|View full text |Cite
|
Sign up to set email alerts
|

Endosome–mitochondria juxtaposition during apoptosis induced by H. pylori VacA

Abstract: The vacuolating cytotoxin (VacA) is an important virulence factor of Helicobacter pylori with pleiotropic effects on mammalian cells, including the ability to trigger mitochondria-dependent apoptosis. However, the mechanism by which VacA exerts its apoptotic function is unclear. Using a genetic approach, in this study we show that killing by VacA requires the proapoptotic Bcl-2 family members BAX and BAK at the mitochondrial level, but not adequate endoplasmic reticulum Ca 2 þ levels, similarly controlled by B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
85
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 49 publications
7
85
0
1
Order By: Relevance
“…Confocal microscopy and quantitative image analysis confirmed that UCD38B initiates a 3.5-fold increase in early and late endosomes colocalizing with mitochondrial regions and that 35% of endosomes appear to be relocated following drug treatment. Similar trafficking between endosomes and mitochondria has been reported following cell death caused by the vacuolating cytotoxin A toxin produced by Helicobacter pylori (Calore et al, 2010), tumor necrosis factor a (Garcia- Ruiz et al, 2002), and Fas (Ouasti et al, 2007).…”
Section: Ucd38b Alters Endosomal Trafficking In Gliomassupporting
confidence: 57%
“…Confocal microscopy and quantitative image analysis confirmed that UCD38B initiates a 3.5-fold increase in early and late endosomes colocalizing with mitochondrial regions and that 35% of endosomes appear to be relocated following drug treatment. Similar trafficking between endosomes and mitochondria has been reported following cell death caused by the vacuolating cytotoxin A toxin produced by Helicobacter pylori (Calore et al, 2010), tumor necrosis factor a (Garcia- Ruiz et al, 2002), and Fas (Ouasti et al, 2007).…”
Section: Ucd38b Alters Endosomal Trafficking In Gliomassupporting
confidence: 57%
“…S7A), it is unlikely that VacA membrane channels formed on the surface of mammalian cells (54) are required for toxin-mediated activation of Drp1-dependent mitochondrial fission. Alternatively, VacA might act directly at mitochondria, as several previous studies reported that a portion of VacA taken up from the cell surface localizes to this organelle (16,29,55). Preliminary studies to address a possible relationship between the location of intracellular VacA and the perturbation of mitochondrial dynamics revealed that VacA localization to mitochondria (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have reported that VacA is capable of causing death of AGS gastric epithelial cells and several other cell lines (5,7,16,39,44). On the basis of the observations that VacA-induced cell death is preceded by the activation of Bax and Bak (75), that VacA can localize to mitochondria (7,21,27,30,70), and that incubation of cells with VacA results in reduction of the mitochondrial transmembrane potential and release of cytochrome c (30,39,70), VacA-induced cell death of these cell lines was classified as an apoptotic process (5,16,44,54,71).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the observations that VacA-induced cell death is preceded by the activation of Bax and Bak (75), that VacA can localize to mitochondria (7,21,27,30,70), and that incubation of cells with VacA results in reduction of the mitochondrial transmembrane potential and release of cytochrome c (30,39,70), VacA-induced cell death of these cell lines was classified as an apoptotic process (5,16,44,54,71). However, these phenomena can occur in cells undergoing either apoptotic or nonapoptotic cell death (33,40,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation